The development of peptide-based vaccine for leptospirosis: In Silico approach / Salwana Binti Othman - Othman, Salwana (2014)

(untitled)
Leptospirosis is a worldwide zoonosis infection caused by Gram-negative bacteria from the genus of Leptospira. Eight pathogenic species of Leptospira have been identified and there are more than 250 serovars that can cause leptospirosis to human and animals. Due to the indistinguishable symptoms of the disease, leptospirosis is often misdiagnosed, resulting to death if antibiotic treatment is not given immediately. Prophylactic vaccine can reduce the mortality rate resulting from the late treatment. However, the existing vaccines for leptospirosis are serovar-specific and can only provide limited protection to human. Therefore, a new and more effective vaccine is urgently needed. The vaccine can be developed in shorter time with reduced cost through rational design and in silico approach by maximizing the use of the abundant information on the sequences of leptospiral antigenic proteins and the growing number of bioinformatics tools. The objective of this research is to perform an in silico analysis to develop a vaccine from the peptide sequence of leptospiral outer membrane protein, LigB. The predicted peptide-based vaccine, which requires experimental validation in the future, is hoped to be effective against all pathogenic serovars of Leptospira and ultimately provide us immunity to leptospirosis.